Effects of dipyrone, meloxicam, or the combination on hemostasis in conscious dogs - Zanuzzo, Felipe S. [UNESP]; Teixeira-Neto, Francisco J.; Thomazini, Camila M. [UNESP]; Takahira, Regina K. [UNESP]; Conner, Bobbi; Diniz, Miriely S. [UNESP] (Veterinary Emergency and Critical Care Society 2015, 2015)
To compare the effects of dipyrone, meloxicam, and of the combination of these drugs on hemostasis in dogs. Prospective, blinded, randomized crossover study. Research laboratory at a veterinary teaching hospital. Six adult dogs. Animals received 4 intravenous treatments with 15-day washout intervals: control (physiological saline, 0.1 mL/kg), meloxicam (0.2 mg/kg), dipyrone (25 mg/kg), and dipyrone-meloxicam (25 and 0.2 mg/kg, respectively). A jugular catheter was placed for drug injection and for collecting samples for whole blood platelet aggregation (WBPA) and thromboelastometry assays at baseline, 1, 2, 3, 5, and 8 hours after treatment administration. The percent change from baseline of lag time and of the area under the curve (AUC) of impedance changes in response to collagen-induced platelet activation were recorded during WBPA. Thromboelastometry-derived parameters included clotting time, clot formation time, alpha-angle, and maximum clot firmness. The buccal mucosal bleeding time was evaluated by a blinded observer at baseline, 1, 3, and 5 hours after treatment injection. No significant changes in WBPA and thromboelastometry were recorded in the control treatment. Dipyrone significantly (P < 0.05) increased the lag time for 2 hours and decreased the AUC for 3 hours after injection. Meloxicam did not alter WBPA. Dipyrone-meloxicam significantly increased lag time for 2 hours and decreased the AUC for 5 hours after treatment injection. Experimental treatments did not differ from the control treatment for thromboelastometry and buccal mucosal bleeding time. While meloxicam does not alter hemostasis by the methods evaluated, dipyrone inhibits platelet aggregation for up to 3 hours. Meloxicam-dipyrone combination causes more prolonged inhibition of platelet function than dipyrone alone. Decreased platelet aggregation induced by dipyrone and dipyrone-meloxicam does not appear to impact the viscoelastic properties of the blood clot nor increase the risk of bleeding in dogs without preexisting hemostatic disorders.
Keywords: Nsaids; Canine; Coagulation; Platelet function; Thromboelastometry